Monitoramento de fatores bióticos e abióticos para controle da qualidade de grãos de milho armazenados em silos verticais - Bilhalva, Nairiane dos Santos (2022)
The grain mass in the storage environment constitutes a dynamic ecosystem, formed by biotic and abiotic elements that are affected both chemically and biologically by several factors. Temperature, relative air humidity and carbon dioxide (CO2) concentration must be monitored, as abnormal variations in any of these factors can create favorable conditions for grain deterioration. Given the above, the objective of this work was to monitor the biotic and abiotic factors that constitute the storage ecosystem, aiming at the early detection of deterioration and quality control of corn grains stored in prototypes of vertical silos. The experiment was carried out in the city of Alegrete/RS from the storage of corn grains with water contents of 16, 14 and 12% in prototypes of vertical silos and monitoring of ambient and intergranular air temperature, ambient and intergranular relative humidity and CO2 concentration in the grain mass. The analyzes carried out for grain quality control were: grain classification, apparent and real specific mass, intergranular porosity, thousand grain weight, electrical conductivity, germination, mycotoxins, centesimal composition, TG, FTIR, soluble protein, lipid acidity, of folder and SEM. Grains stored with water content of 16 and 14% cause a greater increase in intergranular temperature, CO2 concentration and dry matter loss, as well as a decrease in safe storage time, when compared to grains stored with 12%. The physical and physicochemical analyzes were influenced by the water content of the grains and storage time. It is concluded that there was a reduction in the quality of corn grains during storage, corn grains stored with a water content of 12% maintain quality for longer and CO2 monitoring proved to be effective in controlling the quality of corn grains during storage, as it optimizes the detection of grain deterioration.